FST300: Independent Studies / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2009)
Group of student are required to carry out an approved research project under the supervision of on lecturer in the faculty. They are required to submit a research proposal and upon completion of a research project, a bound report as to be submitted to the faculty and the research proposal will be presented. The report together with an oral presentation will be assessed and graded.